Modlitwa apostolska św. Pawła - Szymik, Stefan (Verbum Vitae, 2012)
The present paper presents the most important items of Paul’s apostolic prayer. The inquiry was concerned first with the biblical terms for Paul’s prayers (1) and its formal classification; the main forms are thanksgiving, blessing, and intercession (2). Than there follow some typical features of Paul’s apostolic prayers (3). The last step focuses on the theological aspects of Paul’s prayers, which have theocentric, christological and pneumatical issues (4). The concluding statement is that Paul’s prayer was not a part of his life; it was his whole life in Christ.